Synergistic effects of FGFR1 and PLK1 inhibitors target a metabolic liability in KRAS‐mutant cancer. Issue 9 (8th August 2021) - Yang, Zhang; Liang, Shun‐Qing; Saliakoura, Maria; Yang, Haitang; Vassella, Eric; Konstantinidou, Georgia; Tschan, Mario; Hegedüs, Balazs; Zhao, Liang; Gao, Yanyun; Xu, Duo; Deng, Haibin; et al.
Abstract: KRAS oncoprotein is commonly mutated in human cancer, but effective therapies specifically targeting KRAS‐driven tumors remain elusive. Here, we show that combined treatment with fibroblast growth factor receptor 1 (FGFR1) and polo‐like kinase 1 (PLK1) inhibitors evoke synergistic cytotoxicity in KRAS ‐mutant tumor models in vitro and in vivo . Pharmacological and genetic suppression of FGFR1 and PLK1 synergizes to enhance anti‐proliferative effects and cell death in KRAS ‐mutant lung and pancreatic but not colon nor KRAS wild‐type cancer cells. Mechanistically, co‐targeting FGFR1 and PLK1 upregulates reactive oxygen species (ROS), leading to oxidative stress‐activated c‐Jun N‐terminal kinase (JNK)/p38 pathway and E2F1‐induced apoptosis. We further delineate that autophagy protects from PLK1/FGFR1 inhibitor cytotoxicity and that antagonizing the compensation mechanism by clinically approved chloroquine fully realizes the therapeutic potential of PLK1 and FGFR1 targeting therapy, producing potent and durable responses in KRAS ‐mutant patient‐derived xenografts and a genetically engineered mouse model of Kras ‐induced lung adenocarcinoma. These results suggest a previously unappreciated role for FGFR1 and PLK1 in the surveillance of metabolic stress and demonstrate a synergistic drug combination for treating KRAS ‐mutant cancer. SYNOPSIS: Human cancers driven by oncogenic KRAS mutations are common and among the most difficult‐to‐treat tumors. This study reports a synergistic drug combination by targeting FGFR1 and PLK1 and identifies autophagy as a protective mechanism that limits the efficacy of FGFR1/PLK1 inhibitor therapy in KRAS‐mutant lung cancer, suggesting a novel strategy to treat the daunting disease. FGFR‐ and PLK1‐targeted agents synergize in inhibiting KRAS‐mutant lung and pancreatic cancer cells. FGFR/PLK1 inhibitor therapy targets a metabolic liability by abrogating ROS homeostasis in KRAS‐mutant cancer cells. Autophagy protects against FGFR/PLK1 inhibitor‐induced cytotoxicity. Combined inhibition of FGFR, PLK1, and autophagy shows potent anti‐tumor efficacy in mouse models of KRAS‐mutant lung cancer. Abstract : Human cancers driven by oncogenic KRAS mutations are common and among the most difficult‐to‐treat tumors. This study reports a synergistic drug combination by targeting FGFR1 and PLK1 and identifies autophagy as a protective mechanism that limits the efficacy of FGFR1/PLK1 inhibitor therapy in KRAS‐mutant lung cancer, suggesting a novel strategy to treat the daunting disease.